DLSU 2001 : De La Salle University and national development. - Cruz, Isagani R.;Osteria, Trinidad S. (Malate, Manila, Philippines : De La Salle Universiry Press, 1995)
Murray Rose in his book The University succinctly underscores the need for dynamism in an academic institution within the changing global context. "Tradition without revolution," he writes, "is empty, but revolution without tradition is blind.
1. The Social development research center -- 2. A Social development office in academe -- 3. La Sallian education toward the year 2001 -- 4. The Contribution of religious studies at DLSU -- 5. DLSU economics and national development -- 6. Research at DLSU and national development: performance and imperatives -- 7. The Basic sciences -- 8. The college of engineering -- 9. Issues in computer science -- 10. The College of business and economics -- 11. The Graduate school of business and economics and national development -- 12. Playing the lead role : DLSU in culture and the arts -- 13. DLSU's role in democratization.
Includes index.
Keywords: DEVELOPMENT